A study to determine the association between 5 minute APGAR scores in term newborns and mortality, neonatal encephalopathy and neurodevelopment at eight weeks postnatal age, at the University Teaching Hospital - Chola Ronald (Lusaka: University of Zambia, 2016)
In 1952, Virginia Apgar devised a system of scores as a means of evaluating the physical condition of the newborn immediately after birth. The Apgar score has since been accepted for use to assess newborns in almost all labour wards worldwide.
Dissertation submitted to the University of Zambia in partial fulfilment of requirement for the degree of Master of Medicines in pediatrics.
Includes bibliographic references
Keywords: Infant, newborn, disease; Peadiatric, neurology